Legal bases of interaction of the representative bodies of national states and integration associations bodies - Vasilevich, Grigorii A. (Journal of the Belarusian State University. Law, 2019)
The article analyzes the legal regulation of legal relations in the framework of such integration structures as Commonwealth of Independent States, Union State, the Eurasian Economic Union, to which the Republic of Belarus. The focus is on the interaction of the representative bodies of interstate formations and the Republic of Belarus. Made a number of proposals aimed at improving the efficiency of their work.
Keywords: Commonwealth of Independent States; the Union State; the Eurasian Economic Union; representative bodies; model acts; parliaments; international agreements